Axial behavior of reinforced PP-ECC column and hybrid NSC-ECC column under compression. (15th September 2019) - Li, Fuhai; Feng, Zhihua; Deng, Kailai; Yu, Yongjiang; Hu, Zhiming; Jin, Hesong
Highlights: Pure PP-ECC column and hybrid NSC-ECC column had satisfactory deformability. The self-confining effect from the ECC contributed almost 88% of the confining stress; The hybrid column could deliver the ultimate compressive deformability, up to 0.017. Abstract: Polypropylene engineered cementitious composites (PP-ECC) exhibit superior strength and strain hardening under tensile deformation, which is expected to enhance the anti-cracking performance and self-confinement of the plastic hinge region in structural columns. However, there is still a lack of fundamental studies on the compressive behavior of a reinforcement-confined PP-ECC column. This paper presents a proof-of-concept experimental study on the confined PP-ECC column and hybrid normal strength concrete (NSC)-ECC column. Two sets of reinforcement-confined columns were designed: a pure PP-ECC column and a hybrid C30-PP-ECC column. Then, static compression tests were carried out to prove the effectiveness of the confinement in enhancing the peak strength of the hybrid column with respect to pure PP-ECC columns. However, the deformability improvement was not remarkable, with an increase of only 3.2% from samples containing no stirrups to those containing stirrups at a volumetric ratio of 1.6%. An equation was proposed to predict the peak strength of the confined PP-ECC columns. This equation considered the contribution from the tensile capacity of PP-ECC to the circumferential confining effect of the columns. The hybrid column delivered better deformability but smaller peak strength compared with the pure PP-ECC columns. Some mechanical features of the hybrid column were discussed.